Silent but significant: Functional elucidation of a synonymous ATP7B mutation in Wilson’s disease pedigrees - Zhang, Qi; Xie, Xiaoming; Li, Hairong; Li, Yulei; Huang, Hongyao (Frontiers in Genetics, 2025)
IntroductionWilson’s disease (hepatolenticular degeneration) is a common hereditary neurological disorder. Early diagnosis, particularly the widespread implementation of genetic testing and timely intervention, is crucial for improving the prognosis of this disease. However, limited data exist on genotype-phenotype correlations, thereby impeding accurate early clinical diagnosis.MethodsWhole-exome sequencing was performed on the proband and family members to detect genetic variants associated with the clinical phenotype. Bioinformatics tools (HSF, SpliceAI and ESEfinder 3.0) were used to predict the impact of mutations on the splicing function of precursor mRNA. The in vitro minigene experiment was conducted to verify the impact of the mutation on the splicing function of the precursor mRNA.ResultsWhole-exome sequencing of the proband identified a synonymous variant c.2145C>T (p. Tyr715=) and a pathogenic frameshift mutation c.2304dupC (p. Met769Hisfs*26) in the ATP7B gene, both associated with the clinical phenotype. The frameshift mutation c.2304dupC (p. Met769His fs*26) on the other allele was a known pathogenic variant causing protein truncation. Bioinformatics tools (HSF, SpliceAI, and ESEfinder 3.0) predicted that the c.2145C>T mutation might disrupt nearby splicing sites. In vitro minigene assays confirmed aberrant precursor mRNA splicing caused by ATP7B c.2145C>T (p. Tyr715=) synonymous mutation, resulting in reduced abundance of normal transcripts.ConclusionThe compound heterozygous variants (c.2145C>T and c.2304dupC) in ATP7B likely synergistically contribute to the proband’s abnormal clinical phenotype, aligning with the recessive inheritance pattern of Wilson’s disease.